Investigating the moderating influences of cultural identity and individual personality on online consumer credit adoption in Malaysia - Chiang, Zhi Ling; Leong, Shi Hui; Noor Aimah, Ibrahim (2024)
The growing adoption of online consumer credit among Malaysians raises questions about the factors influencing this behaviour, especially among different personality types and cultural identities. This study investigates the impact of entrepreneurship mindset, debt management strategies, access to credit counselling services, and technology adoption on the adoption of online consumer credit. Drawing from the Social Identity Theory, Theory of Planned Behavior, and Innovation Diffusion Theory, this research explores how cultural identity and individual personality act as moderators in these relationships. A structured questionnaire was developed, comprising 8 sections and 43 questions, and data were collected from 386 respondents. Using SMART PLS4 for SEM analysis, we found that all direct relationships between the independent variables (IVs)—entrepreneurship mindset, debt management strategies, access to credit counselling services, technology adoption—and online consumer credit adoption are significant. Additionally, individual personality, as a moderator, has a direct effect on online consumer credit adoption, whereas cultural identity does not have a direct effect. Following the moderation analysis, the results showed that cultural identity significantly moderated the relationship between technology adoption and online consumer credit adoption, while the other three IVs were not significantly moderated by cultural identity. The second moderator, individual personality, did not significantly moderate the relationship between any of the four IVs and the dependent variable (DV). This study provides a nuanced understanding of how cultural and personal factors shape online consumer credit behaviour, highlighting areas for future research and practical implications for financial service providers.